The influence of e-government system implementation on the accessibility of public health services - Delia Wulandari; Mohamad Arsad Rahawarin; Ahmad Rosandi Sakir (Tamalanrea: Journal of Government and Development (JGD), 2025)
This study examines the effect of implementing an e-government system on the accessibility of public health services at the BPJS Kesehatan Ambon Branch. The research is motivated by the need to transform public services digitally, particularly in archipelagic areas like Ambon, which face geographic obstacles in service distribution. Digital platforms such as Mobile JKN, PANDAWA, and the official BPJS Kesehatan website have been developed to extend service coverage and efficiency. Using a quantitative method with a simple linear regression analysis, this study collected data from 70 respondents who actively use BPJS Kesehatan's digital services. The findings reveal that the implementation of the e-government system has a statistically significant positive impact on health service accessibility. The regression results show a determination coefficient (R²) value of 0.378, meaning 37.8% of the variation in accessibility can be explained by the implementation quality. This confirms the proposed hypothesis that improved e-government implementation enhances access to health services. The regression coefficient for e-government implementation is 0.425. These results underscore the relevance of improving digital infrastructure and educating users to optimize the use of BPJS Kesehatan's e-services, ensuring more inclusive, responsive, and efficient public health service delivery—particularly in regions where physical access remains a challenge due to geographical dispersion.